EVALUASI DALAM PEMBELAJARAN AL-QUR’AN HADIS DI MADRASAH - Zulkipli Nasution (Jurnal Al-Fatih, 2022)
Evaluation of Al-Qur'an Hadith learning is intended for Al-Qur'an Hadith teachers to be able to assess how efficient and effective learning Al-Qur'an Hadith has been so far so that if learning activities are inefficient or not in accordance with the objectives of Al-Qur'an learning -Qur'an Hadith teachers can immediately fix the learning. Evaluation of learning Al-Qur'an Hadith is an activity to assess, measure the level of achievement obtained by students in learning Al-Qur'an Hadith. Learning evaluation also has various functions in the teaching and learning process, among others, as a tool to find out whether students master the knowledge, values and skills that have been given by the Al-Qur'an Hadith subject teacher. Through evaluation, it will be known the level of student achievement in learning activities of Al-Qur'an Hadith, in addition to evaluating Al-Qur'an Hadith as a means of feedback for a teacher, sourced from students and as a measuring tool to determine student learning progress as well as material main learning outcomes reports to parents. In the context of evaluating learning Al-Qur'an Hadith, it is actually the same with the purpose of evaluation in general, the difference is in terms of what you want to achieve or improve and develop from student learning outcomes in terms of material, namely those related to learning Al-Qur'an Hadith. Evaluation of Al-Qur'an Hadith learning in Madrasas places more emphasis on practice or (affective aspects) as a measure of the achievement of learning outcomes. The purpose of evaluating the Al-Qur'an Hadith in Madrasas is to obtain the most appropriate or accurate information in achieving student learning outcomes (instructional goals) so that appropriate follow-up can be sought.